The need for contraception in patients taking prescription drugs: a review of FDA warning labels, duration of effects, and mechanisms of action. Issue 12 (2nd December 2018) - Zhang, Zhanhu; Xu, Lili; Zhang, Zhenyu; Ding, Hongxia; Rayburn, Elizabeth R.; Li, Haibo
ABSTRACT: Introduction : This review provides a guide for the rational use of prescription drugs in patients of reproductive age. Areas covered : A comprehensive retrieval of the labels of FDA-approved drugs was performed to identify drugs where the label recommends contraceptive use during and/or after treatment. The acquired data were analyzed and organized into a table. Contraception was recommended or mandated for 268 single-ingredient drugs. These could be divided into four main categories, with many having effects across several categories: 177 drugs required contraception because they were associated with pregnancy loss or stillbirth, 177 drugs were associated with teratogenesis, 136 were associated with non-teratogenic adverse peri- or postnatal effects on the fetus (e.g. low birth weight), and 44 were associated with decreased efficacy of contraception or a change in ovulatory cycle. We also discuss the period of time contraception is required, as well as the known or hypothesized reasons for the reproductive toxicity of these agents. Expert opinion : We have provided a comprehensive overview of the FDA-approved drugs where the warning labels currently stipulate that contraception should be used. Although other references are available for clinicians, this review provides a useful source of information regarding the single-ingredient prescription drugs that may affect the outcome of pregnancy. This information is particularly relevant for researchers, as it provides an overview of the different drugs with reproductive toxicity, and because it highlights the specific needs for future research. In particular, more work (especially epidemiological studies) is needed to clarify the clinical relevance of these findings, most of which were obtained through animal studies.